Pengaruh Capital Adequacy Ratio, Kepemilikan Asing dan Non Performing Loan terhadap Manajemen Laba Bank - Maryani Kibtiah; Silvi Reni Cusyana (Indonesian Journal of Economics Application (IJEA), 2020)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Foreign Ownership, and Non-Performing Loans (NPL) Against Earnings Management using quantitative methods. This research is causal associative by examining the causal relationship between CAR, Foreign Ownership, and NPL variables on Earnings Management. Samples of 15 banking sector companies were taken by purposive sampling technique and tested using multiple regression analysis techniques with the application of SPSS version 20. The results of the study showed that there was a significant effect of CAR, Foreign Ownership, and NPL on earnings management by 55.5%. The t-test results partially showed one variable that had a considerable influence, namely NPL, with a value of sig, 0,000 <0.05. CAR and Foreign Ownership have an impact but not significantly to Earnings Management that is 0.385> 0.05 and 0.875> 0.05. Besides, the value of sig, 0,000 <0.05, which means there is a significant influence simultaneously (together) between CAR, Foreign Ownership, and NPL on Profit Management.